Exploring the Application of Micellar Drug Delivery Systems in Cancer Nanomedicine - Qi Wang; Keerthi Atluri; Amit K. Tiwari; R. Jayachandra Babu (MDPI AG, 2023)
Various formulations of polymeric micelles, tiny spherical structures made of polymeric materials, are currently being investigated in preclinical and clinical settings for their potential as nanomedicines. They target specific tissues and prolong circulation in the body, making them promising cancer treatment options. This review focuses on the different types of polymeric materials available to synthesize micelles, as well as the different ways that micelles can be tailored to be responsive to different stimuli. The selection of stimuli-sensitive polymers used in micelle preparation is based on the specific conditions found in the tumor microenvironment. Additionally, clinical trends in using micelles to treat cancer are presented, including what happens to micelles after they are administered. Finally, various cancer drug delivery applications involving micelles are discussed along with their regulatory aspects and future outlooks. As part of this discussion, we will examine current research and development in this field. The challenges and barriers they may have to overcome before they can be widely adopted in clinics will also be discussed.